2021
DOI: 10.25104/wa.v45i1.339.49-58
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Potensi Cross Wind Dalam Pembangunan New Yogyakarta International Airport Guna Keselamatan Penerbangan

Abstract: Wind has important role in aviation safety. The aim of the research is to analyze monthly wind profile and crosswind potential in the area of New Yogyakarta International Airport. The method used by installing 4 (four) AWS (Automatic Weather Station) at the end and the middle of the runway during March to September 2017. The results show that the wind patterns in the March-May period have varying directions with an average speed of 5-8 knots. In June -September, the wind pattern blows from the East -Southeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Sardjono [10] predicted monthly crosswind and tailwind potential at CGK airport using Weather Research and Forecasting (WRF) model. Fatkhuroyan [11] discussed crosswind potential at newly built Yogyakarta International Airport (YIA). Saputra [12] present analysis on causes of runway incursion, concluded that rapid changes of wind direction is attributable to unsafe airport operation, emphasizing the need for robust and reliable wind prediction method.…”
Section: Previous Studies In Indonesiamentioning
confidence: 99%
“…Sardjono [10] predicted monthly crosswind and tailwind potential at CGK airport using Weather Research and Forecasting (WRF) model. Fatkhuroyan [11] discussed crosswind potential at newly built Yogyakarta International Airport (YIA). Saputra [12] present analysis on causes of runway incursion, concluded that rapid changes of wind direction is attributable to unsafe airport operation, emphasizing the need for robust and reliable wind prediction method.…”
Section: Previous Studies In Indonesiamentioning
confidence: 99%